Alternative punishment to imprisonment in the Malaysian Shariah Court: Prospects for reforms - Hussin, Nasimah (Institute of Research and Journals, 2017)
Imprisonment is a type of punishments that can be imposed on a Shariah offender in Malaysia. Nevertheless, in practice, Shariah Courts rarely send the convict to prison. They would usually prefer the infliction of fines instead. The question arises as to whether imprisonment should be replaced with alternative punishment which is considered to be more effective to rehabilitate the offender and to reduce the rate of recidivists. Thus this paper will examine the existing legal framework to look at the possibility of the Shariah Courts to consider other punishments as alternative to imprisonment. This paper will also suggest improvements to the system so that the aspects relating to sentencing can be revised.